2016
DOI: 10.1007/s00192-016-3004-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of sexual function in women before and after tension-free vaginal tape operation for stress urinary incontinence

Abstract: This study shows that a woman's sex life does not deteriorate after a TVT operation, that their sexual function improves somewhat, and that results are sustained over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
5
3
0
Order By: Relevance
“…One of the most important parameters that constitute the quality of life of a woman is her sexual life 3,6. It has been reported that due to loss of self-esteem, psychological pressure and dyspareunia caused by contact dermatitis due to urinary contact, UI leads to SD in 25-50% of women with the problem 11. Similarly, in the present study, the majority of the participating women with UI suffered from sexual dysfunction.…”
Section: Discussionsupporting
confidence: 67%
“…One of the most important parameters that constitute the quality of life of a woman is her sexual life 3,6. It has been reported that due to loss of self-esteem, psychological pressure and dyspareunia caused by contact dermatitis due to urinary contact, UI leads to SD in 25-50% of women with the problem 11. Similarly, in the present study, the majority of the participating women with UI suffered from sexual dysfunction.…”
Section: Discussionsupporting
confidence: 67%
“…They have used the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) 30 with questions regarding incontinence during sexual activity and impact of fear of incontinence. 9,18,31,32 These studies reported a decrease in UI related to sexual activity at follow-up, which is in line with the current study. In a study comparing four different surgical interventions treating SUI (MUS was one of the interventions), there was a reduction in UI related to sexual activity 2 years after all interventions.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have evaluated sexual function only in sexually active women up to 10 years after MUS surgery. They have used the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ‐12) 30 with questions regarding incontinence during sexual activity and impact of fear of incontinence 9,18,31,32 . These studies reported a decrease in UI related to sexual activity at follow‐up, which is in line with the current study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In a paper by Detollenaere there was no statistically significant difference in overall sexual functioning between sacrospinous hysteropexy and vaginal hysterectomy with suspension of the uterosacral ligaments after a follow-up period of 24 months [8]. In another study, Glavind showed a significant improvement after different POP operations using native tissue repair [9].…”
Section: Discussionmentioning
confidence: 99%